Role, interests and critics of credit rating agencies - Suzana Baresa; Sinisa Bogdan; Sasa Ivanovic (UTMS Journal of Economics, 2012)
Key role of credit rating agencies is reducing the asymmetry information about credit quality (of governments, business entities or securities) between issuers and investors, and ensuring a common standard of measuring the creditworthiness. Credit rating agencies are engaged in the sale of opinions about creditworthiness in the form of an alphabetical letter or symbol, which represents a unique ranking. Their opinion is not a guarantee, but it largely dictates the costs and the profits in the financial markets. This work shows the influence of credit rating agencies to investors and publishers, and their role as market regulators. Conflict of interest is a fundamental problem, which is caused by their way of doing business, it arises from their two main objectives: profit and market regulation, which will be explored in the work. Looking back in history credit rating agencies often selected goal of making a profit at the cost of market regulation, therefore they have caused the collapse of the market, and founded themselves criticized by the public.
Keywords: G24; G28; 330; credit rating agencies; investment grade; creditworthiness